Boycotting Israel is wrong : the progressive path towards peace between Palestinians and Israelis - Mendes, Philip 1964- (Univ. of New South Wales Press, 2015)
This is the first progressive book to argue that the BDS movement (boycott, divestment and sanctions) is the wrong way to broker peace in the IsraeliuPalestinian conflict. The BDS movement against Israel has gained traction and publicity worldwide. Yet here, Philip Mendes and Nick Dyrenfurth, politically progressive commentators, argue that BDS is too blunt an instrument to use in a such a complex situation. Instead, they propose a solution that supports IsraelAEs existence and Palestinian rights to a homeland, urging mutual compromise and concessions from both sides